Effect of In Vitro Testing Parameters on Ceftazidime-Avibactam Minimum Inhibitory Concentrations. (19th May 2015) - Keepers, Tiffany R.; Gomez, Marcela; Biek, Donald; Critchley, Ian; Krause, Kevin M.
Abstract : Effects of varying in vitro susceptibility testing parameters of the broth microdilution assay on ceftazidime-avibactam MICs were determined and compared to meropenem and piperacillin-tazobactam for 9 Enterobacteriaceae and 4 Pseudomonas aeruginosa isolates. The effect of varying incubation conditions (ambient air or 5% CO2 ), pH of medium, medium composition (cation-adjusted Mueller Hinton Broth with and without laked horse blood and Haemophilus Test Medium), cation content of the medium, and inoculum density were tested. Most variations had no effect on ceftazidime-avibactam MIC values (no more than a 2-fold change). However, acidic pH or high inoculum resulted in 4- to 16-fold changes in MIC, which was similar to those observed for meropenem and piperacillin-tazobactam under these conditions. Overall, this study shows that slight variations in testing parameters during routine MIC testing will likely have no significant effect on ceftazidime-avibactam MIC values.